Pemberian Pupuk Hayati Cair Berformulasi dan NPK Terhadap Pertumbuhan Bibit Tanaman Kakao (Theobroma cacao L.) di Medium Subsoil Ultisol - Imran Maruli Tua Sihombing; Fifi Puspita; Isnaini Isnaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to know response of interaction between liquid biofertilizer formulatied and NPK manure and also to get the best combination treatment on the growth of caccao seedling in subsoil medium of ultisol. The research has been conducted at Experimental Garden of Agriculture Faculty University of Riau from April to September 2017. Using completely randomized design, consisted of two factor with three replication. The first factor was liquid biofertilizier formulated with three level. and the second factor was NPK manure with four level. Data were statistically analyzed using analysis of variance and the means were compared with Duncan's New Multiple Range Test (DNMRT) at level 5%.The result shows that the interaction between biofertilizier formulated and NPK manure increase the growth of caccao seedling in subsoil medium of ultisol. The combination between biofertilizier of palm oil mill waste water formulating 35 ml/seed and 3,75 g/seed gave the best response in increasing plant height, number of leaves and root length of caccao seedling. Keywords : cacao, biofertilizier, NPK.